Performance and well-being of laying hens subjected to various beak trimming methods and rearing systems (Research, Society and Development, 2020)
The aim to evaluate whether different beak trimming methods affected the performance and well-being of laying hens raised in cage and floor systems. During the starter phase, we used a completely randomized design, with three treatments (hot blade beak trimming, infrared beak trimming, and no beak trimming (control)), with four repetitions and in the grower and production phase, we used a factorial arrangement scheme involving two production systems (cage or floor) and three beak management methods (as above). We reared the birds in starter, grower and production phases over a course of 30 weeks. We evaluated productivity, egg quality, behavioral parameters and biochemical variables. In the starter phase, control birds showed higher blood glucose levels (p=0.043). In the grower phase, birds subjected to hot blade beak trimming and control birds showed lower feed intake and better feed conversion. Triglyceride levels were higher in the cage rearing system (p